KORELASI KADAR CRP, TNF-α DAN BONE MINERAL DENSITY DENGAN CARBOXYTERMINAL CROSSLINKED TELOPEPTIDE TYPE I OF COLLAGEN DI PENDERITA ARTRITIS REUMATOID - Kusworini Handono; BP Putra Suryana; Sulistyorini Sulistyorini (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2012)
Rheumatoid Arthritis (RA) is a systemic autoimmune disease accompanied by decreasing bone mass density and ultimately leads toosteoporosis. The cause of decreased bone mass density is still unknown, but the inflammation has been suspected as an important factor.The correlation between the severity of inflammation with the decrease in bone mass density in Indonesian RA patients has not been muchstudied. The purpose of this study was to know the assessment in the correlation between levels of C-reactive protein (CRP), Tumour NecrosisFactor-α (TNFα) and bone mineral density (BMD) with bone resorption marker CTx-1 β-Cross Laps in premenopausal RA patients.Thisobservational study using cross sectional design, was carried out in the Rheumatology Clinic and Central Laboratory of RSSA, Malang fromAugust 2009 until October 2010. All 47 RA patients were diagnosed according to revised of the 1997 American College of Rheumatology(ACR). Measurement of CRP levels uses turbidimetry method, TNF-α and CTX-1 β-Cross Laps levels using ELISA methods and the measurementof BMD using DEXA. The results of this study showed mean levels of CRP were 4.288±1.775 g/L, TNF-α were 322.077±275.248 pg/mLand CTX-1 β-Cross Laps were 0.588±0.139 ng mL. The correlation of CRP and TNF-α levels with CTX-1 β-Cross Laps level were r=0.5832,p=0.453 and r=0.615, p=0.041. Correlation of CTX-1 β-Cross Laps level and Femoral Neck BMD was r=–0.469, p=0.143 and r=0.248,p=0.799 for L average BMD. There was no correlation between CRP level and BMD results with bone resorption marker CTX-1 β-Cross Laps,but there is a significant correlation between high levels of TNFα with CTX-1 β-Cross Laps. It seems that TNF-α appears to be contributed tothe decrease of bone mass density in RA patients.